Red clover (Trifolium pratense) in conservation agriculture: a compelling case for increased adoption. Issue 4 (3rd September 2018) - McKenna, Patrick; Cannon, Nicola; Conway, John; Dooley, John; Davies, William Paul
ABSTRACT: The rapidly growing population will soon require a near doubling of food production. This increase must be achieved in a manner that maintains environmental integrity, preserves public health and resolves food access and distribution equalities. The use of forage legumes in arable rotations can make significant and multidimensional contributions to this sustainable intensification and this paper reviews the potential contribution of red clover ( Trifolium pratense L.), with particular reference to sustainable cereal production in conservation agriculture systems. The use of red clover as a tool in soil fertility-building and the multiple benefits to the cropping system in which it is used is described. The benefits discussed include atmospheric nitrogen fixation, soil conservation, structural soil improvements and a suite of agroecosystem services including increased soil microbial activity, the phytoremediation of polluted soils and the provision of food for pollinators. Reported allelopathic weed suppression by red clover cover crops and the role of modern plant breeding in creating new varieties that further enhance system sustainability is also discussed. Finally, as economic considerations will always impact on adoption rates, the profitability of red clover rotations in terms of silage value and yield benefits is taken into account.